2015
DOI: 10.1111/dmcn.12826
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergies and complexity of neuromuscular control during gait in cerebral palsy

Abstract: AIM Individuals with cerebral palsy (CP) have impaired movement due to a brain injury near birth. Understanding how neuromuscular control is altered in CP can provide insight into pathological movement. We sought to determine if individuals with CP demonstrate reduced complexity of neuromuscular control during gait compared with unimpaired individuals and if changes in control are related to functional ability. METHOD Muscle synergies during gait were retrospectively analyzed for 633 individuals (age range 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
348
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(382 citation statements)
references
References 23 publications
(41 reference statements)
17
348
1
Order By: Relevance
“…EMG activity in most TD and children with CP was well accounted for by four modules (Figures 6A,B). The smaller number of muscle synergies found in children with CP in some previous studies (Steele et al, 2015; Tang et al, 2015; Shuman et al, 2016) may be a consequence of the criterion used to define the minimum number of synergies sufficient to account for overall EMG activity (Hug et al, 2012; Russo et al, 2014) and/or the limited number of recorded muscles (Steele et al, 2013; Zelik et al, 2014; Damiano, 2015). Nevertheless, it is worth noting that the observed phenomenon of widening of basic activation patterns (Figure 6) does not depend on the exact number of modules retained by the specific non-negative matrix factorization procedure (Martino et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…EMG activity in most TD and children with CP was well accounted for by four modules (Figures 6A,B). The smaller number of muscle synergies found in children with CP in some previous studies (Steele et al, 2015; Tang et al, 2015; Shuman et al, 2016) may be a consequence of the criterion used to define the minimum number of synergies sufficient to account for overall EMG activity (Hug et al, 2012; Russo et al, 2014) and/or the limited number of recorded muscles (Steele et al, 2013; Zelik et al, 2014; Damiano, 2015). Nevertheless, it is worth noting that the observed phenomenon of widening of basic activation patterns (Figure 6) does not depend on the exact number of modules retained by the specific non-negative matrix factorization procedure (Martino et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…There are only a few studies that attempted to evaluate the spatiotemporal organization of the spinal locomotor output in CP (Steele et al, 2015; Tang et al, 2015; Shuman et al, 2016) suggesting that individuals with CP may use a simplified control strategy (fewer synergies) compared with unimpaired individuals. However, a more detailed and thorough consideration of multi-muscle coordinated patterns is needed (Damiano, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with CP demonstrate less complexity in their control strategies during gait than their typically developing peers and appear to demonstrate strategies similar to the rhythmic stepping observed in infants [14,15]. This lack of development of mature control strategies may be the underlying mechanism resulting in both impairments in SMC and impairments observed in gait.…”
Section: Discussionmentioning
confidence: 95%
“…Through non-negative matrix factorization (NNMF) of EMG signals from 8 leg muscles, three or four muscle synergies have been identified that appear to account for muscle activation during gait in the majority of healthy persons (Clark et al, 2010; Dominici et al, 2011; Fox et al, 2013). Recent studies, focused on muscle synergies during locomotor tasks, have already yielded promising insight into neuromotor control in persons after stroke (Clark et al, 2010; Gizzi et al, 2011; Roh et al, 2013, 2015; Routson et al, 2013, 2014), in children and adults with incomplete spinal cord injuries (Ivanenko et al, 2009; Fox et al, 2013; Hayes et al, 2014), and in children with cerebral palsy (Steele et al, 2015). …”
Section: Introductionmentioning
confidence: 99%